2007
DOI: 10.1007/bf03347392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sodium/iodide symporter expression with I131 whole body scan uptake between primary and metastatic lymph node papillary thyroid carcinomas

Abstract: The aim of the present study was to evaluate total and membranous Na+/I- symporter (NIS) expressions in papillary thyroid carcinoma (PTC) tissue, correlation of NIS expression between primary and metastatic lymph node (LN) PTC tissues, and relationship of NIS expression with I131 whole body scan (WBS) uptake between primary and metastatic LN PTC tissues by analyzing 17 pairs of primary and metastatic LN PTC tissues. Staining positivity was calculated, and staining intensity was graded as negative (0), weak (1+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…These observations suggest that in thyroid carcinomas, besides transcription regulation, NIS expression appears to be modulated by post-transcriptional events. Therefore, studies of NIS expression by immunohistochemistry (IHC) ( 1 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ), may be, theoretically, more informative since they ‘grab’ NIS a step forward in its biological processing and allow the evaluation of the localization of NIS in the basolateral plasma membrane of follicular cells (the functional transporter).…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that in thyroid carcinomas, besides transcription regulation, NIS expression appears to be modulated by post-transcriptional events. Therefore, studies of NIS expression by immunohistochemistry (IHC) ( 1 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ), may be, theoretically, more informative since they ‘grab’ NIS a step forward in its biological processing and allow the evaluation of the localization of NIS in the basolateral plasma membrane of follicular cells (the functional transporter).…”
Section: Introductionmentioning
confidence: 99%
“…12 Some reports suggested that NIS expression in primary papillary thyroid carcinoma (PTC) tissues could predict NIS expression and radioiodine uptake in matched metastases. [13][14][15] However, the report saying that the defective targeting of NIS and the consequent reduced level of iodine uptake in thyroid cancer are mainly caused by low NIS expression and not by the intracellular localization of overexpressed NIS has raised concerns on the significance of NIS protein expression, as demonstrated by different NIS antibodies. 16 In fact, we recently described a classic papillary thyroid carcinoma (CPTC) patient with positive immunohistochemical staining for NIS but no response to radioiodine therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with primary tumors smaller than 5 mm, recurrences appear in about 1% (7). In follow-up, cervical metastases were discovered more frequently if, at the time of the original operation, the lymph nodes contained carcinoma (8,9). Hay et al found that postoperative 131 I treatments were not followed by statistically fewer nodal recurrences (8), but Chow et al reported that, after ablation, new cervical disease was statistically less common (9).…”
Section: Pierre Bourgeoismentioning
confidence: 99%
“…In follow-up, cervical metastases were discovered more frequently if, at the time of the original operation, the lymph nodes contained carcinoma (8,9). Hay et al found that postoperative 131 I treatments were not followed by statistically fewer nodal recurrences (8), but Chow et al reported that, after ablation, new cervical disease was statistically less common (9). However, overall, recurrences in the absence of ablation therapy were seen in few patients: only 11 (8) and 4 (9).…”
Section: Pierre Bourgeoismentioning
confidence: 99%
See 1 more Smart Citation